Reflexões sobre a contribuição sócio-educativa do projeto de extensão palestras e demonstrações práticas sobre anatomia humana - Capote, Ticiana Sidorenko de Oliveira [UNESP]; Gaspar, Ana Maria Minarelli [UNESP]; Gonçalves, Marcela de Almeida [UNESP]; Conte, Marcelo Brito [UNESP]; Bolini, Paulo Domingos André [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Extension Project "Lectures and Practical Demonstration in Human Anatomy" has been done in the Araraquara School of Dentistry, UNESP. The activities related to the project include lectures on human body, practical demonstrations on cadavers and a visit to the Anatomy Museum. About eight hundred people are attended per year, which includes Elementary School and High School students, public and private schools of Araraquara and region, as well as technical and professionalizing schools, such as nursing, technicians in dental prosthesis, technicians in dental hygiene, dental assistants, civil and military police officers, firefighters, University of the Third Age, etc. The aim of this study was to reflect about the social and educational contributions of this Project. It was verified that the students of the project team are encouraged to develop creativity, ability to speak in public, they have the opportunity to enhance learning and acquisition of new knowledge concerning the anatomy discipline and they can contribute to the community through the transmitted knowledge. The project's contributions to the attended public include educational and social aspects such as motivation of the students of the public and private schools of Araraquara and region to follow the health field careers; prevention of smoking and alcoholism; transmission of ethical and moral fundamentals, and teaching about the human body using different methodologies.

O Projeto de Extensão “Palestras e Demonstrações Práticas sobre Anatomia Humana” é realizado na Faculdade de Odontologia de Araraquara, UNESP. As atividades realizadas relacionadas ao Projeto abrangem palestras sobre corpo humano, demonstrações práticas em cadáveres e visita ao Museu de Anatomia. São atendidas aproximadamente oitocentas pessoas por ano, as quais incluem estudantes de ensino fundamental e médio de escolares públicas e particulares da cidade de Araraquara e região, alunos de curso de auxiliar e técnico em enfermagem, grupo de terceira idade, bombeiros, alunos de curso técnico em prótese dentária. O objetivo do presente trabalho foi realizar reflexões sobre as contribuições sócio-educativas deste Projeto. Pôde-se verificar que os estudantes participantes da equipe do Projeto são estimulados a desenvolverem a criatividade, a habilidade de falar em público, de reforçarem a aprendizagem e adquirirem novos conhecimentos relacionados à Disciplina de Anatomia, além de contribuírem com a comunidade por meio do conhecimento transmitido. As contribuições do Projeto à comunidade atendida abrangem aspectos educativos e sociais, como a motivação dos alunos das redes pública e privada de Araraquara e região a seguirem carreiras da área da Saúde; prevenção do tabagismo e alcoolismo; transmissão de fundamentos de ética e moral e ensinamento sobre o corpo humano por meio de diferentes metodologias.
Keywords: Anatomy; Education; Extension; Anatomia; Educação; Extensão